Humanisierung steigert die Wirksamkeit von CAR-T-Zelltherapien - Tobias D. Deller; Toni Cathomen (BIOspektrum, 2026)
Chimeric Antigen Receptor (CAR) T cells are among the most promising cancer therapeutics of the past decade. However, immunogenic components, often of murine origin, can elicit anti-CAR immune responses that limit their persistence and efficacy. “Humanization” replaces murine sequences with human counterparts, reducing immunogenicity while preserving function. This article discusses mechanisms of CAR T cell rejection and the clinical potential of humanized CAR designs.